Capacitated Lot Sizing Problems in Process Industries - Ramya, Ravi; Rajendran, Chandrasekharan; Ziegler, Hans; Mohapatra, Sanjay; Ganesh, K. (Springer International Publishing : Imprint: Springer, 2019)
XXXV, 196 p. 41 illus.